2018
DOI: 10.2478/hepo-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and growth responses of Mentha piperita to foliar application of biostimulants under greenhouse and field conditions

Abstract: SummaryIntroduction: The biostimulant products are able to improve quality and quantity of medicinal plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
4
3
0
Order By: Relevance
“…The main component of the oil was menthol (Tab. 4) accounting for >50% of the oils, which agrees with the data of Kołodziej [17], and is more than that reported by several other authors [23,[25][26][27]. Our results obtained in this experiment are in line with Higa and Parr's [4] statement that for some soils, even repeated application of effective microorganisms can be ineffective.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The main component of the oil was menthol (Tab. 4) accounting for >50% of the oils, which agrees with the data of Kołodziej [17], and is more than that reported by several other authors [23,[25][26][27]. Our results obtained in this experiment are in line with Higa and Parr's [4] statement that for some soils, even repeated application of effective microorganisms can be ineffective.…”
Section: Discussionsupporting
confidence: 93%
“…Yield of essential oils was higher than that obtained by Węglarz and Załęcki [23] in the natural conditions of Poland. The combined content of essential oils in the peppermint dry herb ranged from 1.85% to 1.90% and was similar to that reported by Pourhadi et al [26], but lower than that by Rosłon et al [24], Karkanis et al [11], and Lafmejani et al [27] and much higher than that given by Zheljazkov et al [25]. It was not dependent on any application of EM preparation (Tab.…”
Section: Discussionsupporting
confidence: 84%
“…In addition to significantly higher levels of the terpenes, the already-discussed 46 , 47 , 50 , 53 , and 55 , compounds such as vanillin ( 4 ), nonanal ( 5 ), 2-/3-methylbutanal ( 10 , 9 ), 2-phenylethanol ( 23 ), and ( Z )-3-hexenol ( 40 ) were also significantly upregulated in mint plants grown under field conditions. High concentrations of terpenes are mainly attributed to the plant’s use of terpenes as defense substances against pathogens, insects, fungi, and bacteria and furthermore as messengers for defense, propagation, and communication purposes in the signal transmission. It was also shown that the concentrations of β-caryophyllene ( 49 ) were statistically significantly higher ( p < 0.05) in the field samples, thus supporting recent research results that β-caryophyllene ( 49 ) is a core component in plant signaling networks . It should also be emphasized that the formation of the aroma compounds and especially the biosynthetically formed odor-active stimuli is strongly influenced by environmental conditions such as temperature, light intensity, photoperiod, humidity, nutrient, and water supply, which can only be controlled under greenhouse conditions and is exposed to large fluctuations under natural conditions. , These results were well in accordance with the literature, and it could be shown that the concentrations of aroma-active compounds were not only in plants like Pelargonium citrosa and Trifolium pratense L. but also in more than 60 different varieties of the genus Mentha , significantly higher under field conditions. , …”
Section: Resultssupporting
confidence: 78%
“…During the growth of the mint plant, the concentration of (+)-pulegone (2) decreased, while the amounts of menthone (13) increased enormously. A similar phenomenon could be observed for limonene (53): a tremendous increase could be observed up to full bloom before that compound was converted by several enzymatic reactions into aroma compounds like (R,S)-carvone (12), dihydrocarveol (36), isopulegol (34), and (+)-pulegone (2). Large differences in concentration were observed, especially for the stress metabolite (+)-menthofuran (48).…”
Section: ■ Results and Discussionsupporting
confidence: 61%
See 1 more Smart Citation